2016
DOI: 10.1007/s40262-016-0432-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Pharmacodynamics of Lenalidomide

Abstract: Lenalidomide is a lead therapeutic in multiple myeloma and deletion 5q myelodysplastic syndromes and shows promising activities in other hematologic malignancies. This article presents a comprehensive review of the clinical pharmacokinetics and pharmacodynamics of lenalidomide. Oral lenalidomide is rapidly and highly absorbed (>90 % of dose) under fasting conditions. Food affects oral absorption, reducing area under the concentration–time curve (AUC) by 20 % and maximum concentration (C max) by 50 %. The incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 61 publications
(138 reference statements)
2
66
0
Order By: Relevance
“…These molecules have similar molecular structures; however, their often subtle chemical differences alter not only their substrate specificities but also their PK profiles. For example, lenalidomide is not subject to significant CYP‐based or conjugative metabolism and is instead eliminated mostly through renal excretion of the unchanged drug; in contrast, pomalidomide is primarily metabolized by CYP1A2 and CYP3A, with a low fraction excreted in urine as unchanged drug . Pomalidomide exposures when administered with the CYP3A inhibitor ketoconazole were 118.8% and 107.3%, for AUC and C max , respectively, of that when administered alone .…”
Section: Discussionmentioning
confidence: 99%
“…These molecules have similar molecular structures; however, their often subtle chemical differences alter not only their substrate specificities but also their PK profiles. For example, lenalidomide is not subject to significant CYP‐based or conjugative metabolism and is instead eliminated mostly through renal excretion of the unchanged drug; in contrast, pomalidomide is primarily metabolized by CYP1A2 and CYP3A, with a low fraction excreted in urine as unchanged drug . Pomalidomide exposures when administered with the CYP3A inhibitor ketoconazole were 118.8% and 107.3%, for AUC and C max , respectively, of that when administered alone .…”
Section: Discussionmentioning
confidence: 99%
“…However, PK differences appeared to exist between HVs and patients for oral immunomodulatory drugs. Plasma exposure (AUC) to lenalidomide has been shown to be higher in patients than in HVs, even when renal function was comparable . Interestingly, PopPK analysis for pomalidomide, a similar oral immunomodulatory drug, suggested that peripheral distribution of pomalidomide was greater in MM patients than in HVs …”
mentioning
confidence: 99%
“…Plasma exposure (AUC) to lenalidomide has been shown to be higher in patients than in HVs, even when renal function was comparable. 21 Interestingly, PopPK analysis for pomalidomide, a similar oral immunomodulatory drug, suggested that peripheral distribution of pomalidomide was greater in MM patients than in HVs. 22 The current analysis aimed to develop a PopPK model to quantitatively describe the PK disposition of lenalidomide and to investigate whether disease or other intrinsic factors alter the disposition of lenalidomide.…”
mentioning
confidence: 99%
“…Lenalidomide is excreted by the kidney, and the drug-metabolizing enzyme cytochrome P450 (CYP) is not involved in this metabolizing process (7,8). Lenalidomide is known to be a poor substrate of P-glycoprotein (P-gp), but no clinically significant drug interactions between lenalidomide and P-gp substrates and inhibitors have been observed (9).…”
Section: Introductionmentioning
confidence: 99%